Tetracycline impregnated bone grafts in the management of peri-implantitis and guided bone regeneration around dental implants: A systematic review - Priyanshu Kumar Shrivastava; Arifa Mahmood; Shubham Datta; Poonam Sengar; Deborah Sybil (Saudi Dental Journal)
Background: Rehabilitation of dental arches with the help of dental implants has been revolutionary and a significant part of research is devoted to increasing its success rate. One of the most common causes of failure of dental implants is peri-implantitis caused due to microbial invasion. Newer strategies are being adapted for the treatment of peri-implantits and recent surgical management with the help of antibiotic-impregnated bone grafts shows a promising future. Aim and objectives: This study aimed to test the efficacy of bone grafts incorporating tetracycline and its derivatives in the treatment of peri-implantits and guided bone regeneration with the estimation of clinical and radiographic parameters. Methods: A thorough search was made on eminent databases such as PubMed, Embase, Scopus, and Cochrane Library database for published literature on tetracycline impregnated bone grafts used either in the management of peri-implantitis or for guided bone regeneration around dental implants.The measures of outcome were clinical attachment loss or probing depth around dental implants and radiographic bone height. Results: Nine potentially eligible full-text published articles including case reports, case series, observational studies, and randomized controlled trials were selected for review. Most of the studies reviewed; reported a reduction in probing depth and an increase in bone height and density after placement of tetracycline bone grafts around the dental implant. Conclusion: The incorporation of tetracycline into the bone grafts shows promising results as an agent of local delivery around dental implants in the management of peri-implantitis and for guided bone regeneration. Future trials are required to produce a body of evidence and to facilitate the translation of this procedure into clinical practice.